Frequência de patógenos na pele e meatos de tetas de bovinos - Eurico de Faria, José; Britto Figueiredo, José; dos Santos, José Lúcio (Revista Ceres, 2025)
Bacteriological examinations of the skin and external galactophorus duct of 35 teats, not washed, from nine cows in lactation, revealed the presence of mi- croorganisms considered pathogenic to the mammary gland on the skin of 31 teats (88.6%) and on the ducts of 16 (45.7%). These high frequencies demonstrate the importance of these areas as reservoirs.